Thyroid dysfunction and hypertensive disorders in pregnancy: a retrospective study stratified by gestational age and maternal thyroid profile - Thakur, Meenakshi; Rana, Deepti; Verma, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Thyroid dysfunction has been increasingly implicated in the development of hypertensive disorders in pregnancy (HDP), though its influence on gestational age of onset, fetal outcomes, and disease severity remains underexplored. The roles of maternal parity, intrauterine growth restriction (IUGR), and antihypertensive management strategies in this context are also not well established. Methods: A retrospective study was conducted at a tertiary care center in North India over 3 years (2022–2025), including pregnant women diagnosed with HDP after 20 weeks of gestation. Thyroid function tests (TSH, FT4) were correlated with HDP type, gestational age at onset, parity, presence of IUGR, and antihypertensive therapy used. Results: Among 384 women with HDP, 114 (29.7%) had thyroid dysfunction 96 (25%) with subclinical and 18 (4.7%) with overt hypothyroidism. Thyroid abnormalities were more prevalent in women with early-onset HDP (<34 weeks) and in primigravidae. IUGR was observed in 41.2% of patients with thyroid dysfunction compared to 22.9% in euthyroid women (p<0.01). Subclinical hypothyroidism was strongly associated with preeclampsia and eclampsia. The most commonly prescribed antihypertensive agents were labetalol (74.1%) and nifedipine (62.5%), with higher use of dual therapy in patients with overt hypothyroidism. Conclusions: Thyroid dysfunction, particularly subclinical hypothyroidism, is significantly associated with early-onset and severe hypertensive disorders, higher incidence of IUGR, and increased need for combination antihypertensive therapy. Routine thyroid screening in antenatal care, especially in primigravidae, may facilitate early risk identification and targeted management.